أثر تطبيق معايير الحكم الرشيد على الإصلاح الإداري في دولة الإمارات العربية المتحدة = The impact of the application of good governance standards on administrative reform in the UAE = Kesan pelaksanaan standard pentadbiran yang baik pada reformasi pentadbiran di Emiriah Arab Bersatu - Abdel Salam, El Fatih Abdullahi (IIUM Press, International Islamic University Malaysia, 2018)
تعالج هذه الدراسة أثر تطبيق معايير الحكم الرشيد على الإصلاح الإداري في دولة الإمارات العربية المتحدة، وكيف ساهم التوجه الحكومي للدولة في تطبيق الحكم الرشيد وتحقيق قدر لا بأس به من مؤشرات نوعية في الادارة العامة والقطاع العام ورضا المواطنين ومكافحة الفساد الذي يعد من أهم الاسباب التي تعيق التنمية وتهدر موارد الدولة، ولتحقيق أهداف الدراسة تم استخدام المنهج الوصفي التحليلي. وقد توصلت الدراسة إلى مجموعة من النتائج أهمها: أن هناك تقدماً نسبياً حققته دولة الإمارات في هذا المجال لاسيما في مجال مكافحة الفساد وتحقيق مراتب عالمية متقدمة بالإضافة إلى تطور الأداء الحكومي بقدر كبير، الا أن عدداً من التحديات يتطلب المزيد من الاجراءات لتحقيق الشفافية وتفعيل المساءلة. ************************************************************* This study addresses the impact of the application of good governance standards on administrative reform in the UAE, and how the government's approach to the implementation of good governance contributed to achieving a good number of qualitative indicators in public administration, public sector, citizen satisfaction and combating corruption. The later is one of the main reasons that has hindered development and wasted resources of the state. The study reached a number of results, the most important of which is that there is a relative progress achieved by the UAE in this field, especially in the field of combating corruption and achieving advanced international rankingsin addition to the development of government performance. The governance requires further measures to achieve transparency and accountability. ********************************************************** Kajian ini mengenaikesan pelaksanaan standard pentadbiran yang baik pada reformasi pentadbiran di Emiriah Arab Bersatu, dan bagaimana pendekatan kerajaan untuk pelaksanaan pentadbiran yang baik yang telah menyumbang kepada pencapaian beberapa petanda kualitatif dalam pentadbiran awam, sektor awam, kepuasan rakyat dan memerangi rasuah, yang merupakan salah satu sebab utama yang telah menghalang proses pembangunan dan mensia-siakan sumber-sumber negeri. Kajian ini telah mencapai beberapa hasil, yang terpenting di mana terdapatkemajuan yang relatif yang dikecapi Emiriah Arab Bersatu dalam bidang ini, terutamanya dalam bidang memerangi rasuah dan mencapai kemajuan di peringkat antarabangsa dan perkembangan prestasi kerajaan. Langkah-langkah selanjutnya diperlukan untuk mencapai ketelusan dan akauntabiliti.